I Ask for Justice : Maya Women, Dictators, and Crime in Guatemala, 1898-1944 - Carey, David, Jr., 1967- (Book collections on Project MUSE., 2013)
This study of the Guatemalan legal system during the regimes of two of Latin America's most repressive dictators reveals the surprising extent to which Maya women used the courts to air their grievances and defend their human rights.